An overview of jellyfish aquaculture: for food, feed, pharma and fun. (22nd July 2021) - Duarte, Inês Matos; Marques, Sónia Cotrim; Leandro, Sérgio Miguel; Calado, Ricardo
Abstract: Interest on jellyfish research has significantly increased over the last two decades, mostly driven by the potential benefits of their high‐end uses. Recent efforts have been put forward towards the commercial use of scyphozoan jellyfish, although the pipeline leading to their full exploitation is still at an early stage of development. Indeed, further research and several technical advances are still required to expand the use of these bioresources to a larger and more sustainable scale. Here, we describe the state of the art of culture systems already available to farm these organisms throughout the different stages of their life cycle and provide an overview of the potential applications of jellyfish aquaculture for food, feed, as source of bioactive compounds for pharmaceutical and other biotechnological applications, as well as to supply the marine aquarium trade. Overall, this work aims to raise awareness on the relevance that jellyfish will likely play on the development of sustainable blue bioeconomy frameworks fostering a sustainable valorisation of marine living resources.